Augmenting customer experience with SharePoint Online : building portals and practices to improve usability - Waghmare, Charles David (Apress, 2020)
Build, enrich, and transform customer experience using SharePoint Online. This book will discuss different SharePoint Online approaches that you can use to enhance customer experience, including digital portals, enterprise content management, Microsoft Teams and much more. Augmenting Customer Experience with SharePoint Online starts with an introduction to SharePoint Online features you can adopt to create better digital customer experience and transformation. Next, you will learn about augmentation for user and customer experience followed by guidelines and methods to develop smart and intelligent portals. Moving forward, you will cover enterprise and web content management in detail along with the challenges and benefits of using SharePoint Online. The partner ecosystem is discussed next with a detailed discussion on working with suppliers, partners, and vendors. Along the way, you will see how to create smart solutions using SharePoint Online and how to manage customer references. Finally, you will go through the use of SharePoint Online in different business sectors with the help of case studies. After reading the book, you will be able to adopt SharePoint Online features to augment customer and user experience. You will: Augment customer experience Create smart and intelligent portals for various business needs Efficiently manage enterprise and web content Enhance your partner ecosystem for better collaboration Build SharePoint Online solutions.